2006
DOI: 10.1111/j.1528-1167.2006.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy in Women with Epilepsy: A Randomized, Double‐Blind, Placebo‐Controlled Study

Abstract: Summary:Purpose: Previous reports have suggested that hormone replacement therapy (HRT) could increase seizure activity in women with epilepsy. We sought to determine whether adding HRT to the medication regimen of postmenopausal women with epilepsy was associated with an increase in seizure frequency.Methods: This was a randomized, double-blind, placebocontrolled trial of the effect of HRT on seizure frequency in postmenopausal women with epilepsy, taking stable doses of antiepileptic drugs (AEDs), and within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 19 publications
3
69
0
3
Order By: Relevance
“…However, in patients with epilepsy, estrogens being proconvulsant, estrogen therapy might enhance the seizure frequency [Harden et al, 2006]. A series of findings by Women's Health Initiative Memory Study (WHIMS) suggested lack of efficacy in the treatment of cognitive decline or dementia with exogenous estrogens as well as combination therapy Shumaker et al, 2003Shumaker et al, , 2004Espeland et al, 2004].…”
Section: Hormone Replacement Therapymentioning
confidence: 99%
“…However, in patients with epilepsy, estrogens being proconvulsant, estrogen therapy might enhance the seizure frequency [Harden et al, 2006]. A series of findings by Women's Health Initiative Memory Study (WHIMS) suggested lack of efficacy in the treatment of cognitive decline or dementia with exogenous estrogens as well as combination therapy Shumaker et al, 2003Shumaker et al, , 2004Espeland et al, 2004].…”
Section: Hormone Replacement Therapymentioning
confidence: 99%
“…A double-blind, randomized, placebo-controlled trial was performed with three study groups: women taking singledose combination HRT (0.625 mg of conjugated equine estrogens [CEE] plus 2.5 mg of MPA, or CEE/MPA) daily, double-dose CEE/MPA, or placebo [39]. Five of seven subjects taking double-dose CEE/MPA had a worsening seizure frequency, compared with four of eight taking single-dose CEE/MPA and one of six taking placebo (P= 0.05).…”
Section: Hormone Replacement Therapy In Epilepsymentioning
confidence: 99%
“…As epilepsy is affected by sex steroids, careful consideration must be given to the regimen used. However, the data are extremely limited (Harden et al, 2006;Shen & Stearns 2009). The details of the only randomized trial double-blind, placebocontrolled trial are now described (Harden et al, 2006).…”
Section: Epilepsy and Menopausementioning
confidence: 99%
“…However, the data are extremely limited (Harden et al, 2006;Shen & Stearns 2009). The details of the only randomized trial double-blind, placebocontrolled trial are now described (Harden et al, 2006). This was undertaken in postmenopausal women with epilepsy who are taking stable doses of AEDs and are within 10 years of their last menses.…”
Section: Epilepsy and Menopausementioning
confidence: 99%